Respuesta :
Answer: x= 10. y= 2
Step-by-step explanation:
From the first statement :
[tex]x + y = 12[/tex]
And from the second statement :
[tex]x - 2y = 6[/tex]
combining the two equations we have :
[tex]x + y = 12[/tex] .......................... equation 1
[tex]x - 2y = 6[/tex] .......................... equation 2
solving the system of simultaneous linear equation by substitution method , from equation 1 , make [tex]x[/tex] the subject of the formula , that is
[tex]x = 12 - y[/tex] ........................... equation 3
substitute [tex]x = 12 - y[/tex] into equation 2 , then we have
[tex]12 - y - 2y = 6[/tex]
[tex]12 - 3y = 6[/tex]
[tex]12 - 6 = 3y[/tex]
[tex]6 = 3y[/tex]
Therefore : [tex]y = 2[/tex]
substitute [tex]y = 2[/tex] into equation 3 to find the value of x , that is
[tex]x = 12 - y[/tex]
[tex]x = 12 - 2[/tex]
[tex]x = 10[/tex]